(untitled) (Global Journal of Human-Social Science, 2021)
Academic genre analysts have over the last few decades preoccupied themselves with the description of rhetorical organisation of different academic genres. This is done with a view to providing writers (most especially young entrants into academic discourse community) with knowledge on academic genre literacy. Extant literature reveals that generic structural elements of arts-based research article abstracts have not been much explored using generic comparative analytical approach/perspective and this creates a research vacuum in the literature. This study therefore fills the vacuum as it carries out a comparative study of Generic Structural Elements in Research Article Abstracts of Selected Arts-Based Disciplines. This is done with a view to determining the generic structural variations across disciplines. The study utilised as data three hundred abstracts, 100 from each group, purposively selected from 27 journals in Languages and Communication (LC), 13 in Literary and Creative Arts (LCA) and 25 in Cultural Studies and Philosophy (CSP) published between 2001 and 2010. The journals selected are domiciled in universities in the inner circle (countries where English is spoken as mother tongue). The generic structural elements of these abstracts are comparatively analysed using insights from the Generic Structural Potential analytical tool of SFG.